Orbital Metastasis of Breast Cancer Mimicking Invasive Fungal Rhinosinusitis - Mayara Tabai; Igor Moreira Hazboun; Emerson Taro Inoue Sakuma; Marcelo Hamilton Sampaio; Eulalia Sakano (Case Reports in Otolaryngology)
Introduction. A range of traumatic, vascular, inflammatory, infectious, and neoplastic processes can affect the orbit and its structures. In the area of otolaryngology, the rhino-orbital-cerebral involvement of invasive fungal rhinosinusitis can affect the orbit, which may look like initially a rhinosinusitis or even mimic malignancy. Case Presentation. Female patient, 32 years old, with headache and ocular proptosis. She was using prednisone in immunosuppressive doses for a year and had breast cancer treated three years earlier. The initial CT scan showed opacification of the sphenoid and ethmoid sinuses, left intraorbital involvement and contrast impregnation in the cavernous sinus. The biopsy resulted positive for invasive ductal carcinoma of the breast. Discussion. The initial CT scan of our patient showed both signs of early changes of invasive fungal rhinosinusitis (IFR) and possible metastatic involvement. The intracranial extension and ocular involvement are usually the most common signs of IFR (first hypothesis). Among metastases at the orbit and the eye, breast and lung carcinomas are the most frequent. Conclusion. Although several studies on the differential diagnosis of orbital lesions exist, especially when it concerns the involvement of the nasal cavity, the diagnosis by imaging is still a challenge.